Design and development of vector antennas - Han, Chenjiang (2013)
Loop antennas are commonly adopted in military use to find the direction of arrival (DoA) of an incoming signal. The DoA can be obtained with sufficient data and proper calculation. However, the quality of the signal power is usually significantly affected by the noise and the loss in transmission line. Therefore, this project follows up last attempt to match the impedance of antenna with transmission line in order to mitigate the reflection loss.